1990
DOI: 10.1007/bf01972987
|View full text |Cite
|
Sign up to set email alerts
|

The mycotoxin ochratoxin A is a substrate for phenylalanine hydroxylase in isolated rat hepatocytes and in vivo

Abstract: Ochratoxin A (OTA), is a myocotoxin contaminating food and feed stuffs, consisting of a chlorinated dihydroisocoumarin linked through a 7-carboxyl group to L-phenylalanine by an amide bond. When OTA (0.12-1.4 mM) is incubated with freshly isolated rat hepatocytes, it inhibits both the hydroxylation of phenylalanine (0.05 mM) to tyrosine, catalyzed by phenylalanine hydroxylase and the subsequent metabolism of tyrosine as measured by homogentisate oxidation. The IC50 of OTA for phenylalanine hydroxylation is 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Several studies have demonstrated that OTA inhibits protein synthesis via inhibition of phenylalanyl-tRNA synthetase interfering with peptide elongation (Creppy et al 1984(Creppy et al , 1990Dirheimer and Creppy 1991). Interestingly, in our data set, phenylalanyl-tRNA synthetase, alpha subunit (Farsa) was decreased in all studies (Table 4B).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that OTA inhibits protein synthesis via inhibition of phenylalanyl-tRNA synthetase interfering with peptide elongation (Creppy et al 1984(Creppy et al , 1990Dirheimer and Creppy 1991). Interestingly, in our data set, phenylalanyl-tRNA synthetase, alpha subunit (Farsa) was decreased in all studies (Table 4B).…”
Section: Discussionmentioning
confidence: 99%
“…He also showed that OTA inhibited intramitochondri:a.1 phosph:a.te transport, resulting in dcteriOTalion of the mitochondria. The f:a.ilure of OTA 10 deplete ATP in Tat hepatocyles 10 observed by Creppy et al (1990), and the ability of 011(, which is non-loxic. 10 inhibit mitochondrial respiration more effectively than OTA (Moore and Truelove, 1970) would suggest that mitochondrial effects probably did not contribute to the toxic effects of OTA.…”
Section: 18mentioning
confidence: 93%
“…It has a number of toxic effects that may be the result of inhibition of ATP synthesis; enhanced lipid peroxidation (LPO) and inhibition of protein synthesis (Marquardt and Frohich, 1992). Ochratoxin A inhibits protein synthesis by competition with phenylalanine in the aminoacylation reaction of phenylalanine-tRNA (Bunge et al, 1978) and phenylalanine hydroxylase activity (Creppy et al, 1990), which could lead to impairment of the synthesis of DOPA, dopamine and derived compounds. Ochratoxin A also induces oxidative damage by enhancing LPO (Rahimtula et al, 1988;Omar et al, 1991).…”
Section: Introductionmentioning
confidence: 99%